2017
DOI: 10.1186/s13089-017-0057-0
|View full text |Cite
|
Sign up to set email alerts
|

Point-of-care ultrasound identification of pneumatosis intestinalis in pediatric abdominal pain: a case report

Abstract: We describe a case report of an infant with intussusception who presented to a pediatric emergency department with diarrhea and increased irritability. Pneumatosis intestinalis (intra-mural air) detected on point-of-care ultrasonography (but not apparent on plain abdominal radiographs) alerted the emergency physicians towards the severity of disease process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Moreover, US is the first-choice diagnostic test in the evaluation of children with suspected intussusception and pyloric stenosis with an overlap sensitivity and specificity when performed by imaging specialists, junior residents or pediatric emergency physicians [ 29 ]. POCUS can rule in the diagnosis of intussusception and could be useful in the estimation of blood flow, in the identification of free fluid or echogenic foci that could suggest a failure in intussusception reduction or complications [ 17 , 30 ]. Concerning pyloric stenosis, frequently suspected in projectile vomiting, there is no currently definitive consensus regarding absolute measurements [ 29 ] and ulterior research is needed in this field.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, US is the first-choice diagnostic test in the evaluation of children with suspected intussusception and pyloric stenosis with an overlap sensitivity and specificity when performed by imaging specialists, junior residents or pediatric emergency physicians [ 29 ]. POCUS can rule in the diagnosis of intussusception and could be useful in the estimation of blood flow, in the identification of free fluid or echogenic foci that could suggest a failure in intussusception reduction or complications [ 17 , 30 ]. Concerning pyloric stenosis, frequently suspected in projectile vomiting, there is no currently definitive consensus regarding absolute measurements [ 29 ] and ulterior research is needed in this field.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have shown that bedside ultrasound imaging is successful abdominal organs pathologies within adults and children. [11][12][13][14] A study that investigated the role of US performed by EPs in detecting the various causes of AAP found a 76% rate of accurate diagnosis. 3 In another study in patients with nonspecific abdominal pain, the accurate diagnosis of EPs was found a 45%.…”
Section: Discussionmentioning
confidence: 99%
“…POCUS abdomen has been shown to aid and expedite the diagnosis in patients with abdominal trauma with hemoperitoneum, characterize systemic hypoperfusion and shock, detect gallstones, acute cholecystitis, and diagnose ureterolithiasis and assess for pyelonephritis [7][8][9][10]. It can be a useful adjunct for bedside diagnosis of digestive tract diseases such as intussusception, appendicitis, small bowel obstruction, and bowel perforation [3,[11][12][13]. POCUS can be a valuable imaging tool for assessing a pediatric patient with abdominal pain, in whom stringent adherence to the principle of ALARA is paramount [14].…”
Section: Discussionmentioning
confidence: 99%